ANALYSIZING ERRORS OF INFLECTIONAL AFFIXES ON STUDENTS’ WRITINGS - Ahmad Sunandar (English Education Department at FKIP Nommensen University, 2022)
This research aimed to identify what error of inflectional affixes was the most frequently appeared on students’ writings and what error of inflectional affixes was the least frequently appeared on students’ writings. The approach of research was qualitative method with descriptive analysis to analyze the data. The data were taken from students’ writings made by 111 second semester students of Indonusa Polytechnic Surakarta majoring in health information management. This research was to perform the percentage of error of inflectional affixes on students’ writings. The percentage of plural -s/es was 58,46 %, third person present singular -s/es was 20 %, past tense –ed was 6,15 %, past participle -en/ed was 6,15 %, progressive –ing was 3,08 %, possessive –‘s was 3,08 %, superlative –est was 1,68 % and comparative –er was 1,40 %. Referring to the percentages of the research, the researcher concluded that the error of inflectional affixes which the most frequently appeared was plural –s/es with the percentage 58,46 %, and the error of inflectional affixes which the least frequently appeared was comparative –er with the percentage 1,40 %. Mastering inflectional affixes is important in order to make precise sentences. Therefore, students should perform well in applying inflectional affixes.